Catalogue of the Lichenized and Lichenicolous Fungi of Bosnia and Herzegovina - Bilovitz, Peter O. (2010)
The catalogue is based on a comprehensive evaluation of 152 published sources. It includes 624 species (with 4 subspecies and 13 varieties) of lichenized and 17 species of lichenicolous Ascomycota, as well as 9 non-lichenized Ascomycota traditionally included in lichenological literature.